Taxonomic review of the genus Rhodostrophia Hübner, 1823 (Geometridae: Sterrhinae) in Iran - Rajaei, Hossein; Hausmann, Axel; Trusch, Robert (Zootaxa, 2022)
So far, the species of the genus Rhodostrophia Hübner, 1823 (Geometridae), their diagnostic characters and their distribution in Iran have not been investigated in detail. Moreover, some species were misunderstood by earlier authors. To solve these problems, a survey of the Iranian Rhodostrophia species based on over 1700 specimens has been executed. The type series of all species known from Iran were examined. Additionally extensive material from different museums and private collections was morphologically studied and compared with the type material. DNA-barcoding was used as an independent line of information and the results were compared with the morphological data. Examination of the type material revealed that R. cuprinaria (Christoph, 1876) was misinterpreted for a long time. The taxon R. nubifera Brandt, 1941 syn. nov. is a younger synonym of Hugo Christoph’s R. cuprinaria, which was misidentified by himself in his later publications. An available name for “R. cuprinaria” in the old, erroneous sense is R. phaenicearia (Hampson, 1907). Three subspecies were recognized for R. terrestraria, including R. terrestraria farsi ssp. nov. Additionally, R. terrestraria furialis Brandt, 1941 syn. nov. is here regarded as junior synonym of R. terrestraria (Lederer, 1869); Rhodostrophia nubifera nubifera Brandt, 1941 syn. nov. and R. nubifera klapperichi Wiltshire, 1966 syn. nov. are here regarded as junior synonyms of R. cuprinaria (Christoph, 1876). R. abscisaria chlorotica Wiltshire, 1967 syn. nov. is downgraded to synonymy of R. abscisaria Brandt, 1941 and R. peripheres debilis Wiltshire, 1949 syn. nov. to synonymy of R. peripheres Prout, 1938. Rhodostrophia vahabzadehi sp. nov. is described as a new species. In total, 15 species are regarded as valid for the fauna of Iran. External and internal morphological characters for all examined species are illustrated. Distribution data are shown on maps for of all species. An updated checklist is presented for the Iranian representatives of the genus Rhodostrophia.